2017
DOI: 10.1186/s12887-017-0822-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of mobile phones and text messaging to decrease the turnaround time for early infant HIV diagnosis and notification in rural Zambia: an observational study

Abstract: BackgroundEarly infant diagnosis of HIV infection is challenging in rural sub-Saharan Africa as blood samples are sent to central laboratories for HIV DNA testing, leading to delays in diagnosis and treatment initiation. Simple technologies to rapidly deliver results to clinics and notify mothers of test results would decrease many of these delays. The feasibility of using mobile phones to contact mothers was evaluated. In addition, the first two years of implementation of a national short message service (SMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Both aimed to have quicker infant ART initiation and both reported positive outcomes. (Finocchario-Kessler et al, 2014;Sutcliffe et al, 2017). The Kenyan study assessed the impact of faster laboratory result distribution through SMS technology to facilitate quicker result dissemination of HIVinfected infants to fast track their initiation on ART, and found that initiation had been reduced from 38 to 7 median days (Finocchario-Kessler et al, 2014).…”
Section: Infant Art Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both aimed to have quicker infant ART initiation and both reported positive outcomes. (Finocchario-Kessler et al, 2014;Sutcliffe et al, 2017). The Kenyan study assessed the impact of faster laboratory result distribution through SMS technology to facilitate quicker result dissemination of HIVinfected infants to fast track their initiation on ART, and found that initiation had been reduced from 38 to 7 median days (Finocchario-Kessler et al, 2014).…”
Section: Infant Art Initiationmentioning
confidence: 99%
“…The Kenyan study assessed the impact of faster laboratory result distribution through SMS technology to facilitate quicker result dissemination of HIVinfected infants to fast track their initiation on ART, and found that initiation had been reduced from 38 to 7 median days (Finocchario-Kessler et al, 2014). The other study in Zambia found that by offering mothers owning mobile phones the option of being contacted by study staff when their child's test results were available, infants in the intervention group were initiated on ART at a median of 66 days compared to the previous median of 101 days without the intervention (Sutcliffe et al, 2017).…”
Section: Infant Art Initiationmentioning
confidence: 99%
“…Testing at sites in Macha and Choma represents the testing experience for clinics located far from the central laboratory. However, as testing at the central laboratory in Lusaka was performed as a study procedure and the process was managed by study staff, the turnaround times for this study were significantly shorter than those observed under routine conditions in this area [19][20][21]. In all study areas, the time to get results to the mother was longer than the 4 weeks recommended by WHO [3].…”
Section: Discussionmentioning
confidence: 98%
“…SMS interventions have been evaluated across sub-Saharan Africa for their capacity to improve medication adherence [26], support the dissemination of lab results [27], and reduce missed clinic visits [28]. However, with few exceptions [29], the existing literature does not address how often SMS are received, understood, and retained by participants.…”
Section: Discussionmentioning
confidence: 99%
“…Median age among adult participants was 27 years of age (interquartile range (IQR) [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Step 2: SMS Received…”
Section: Study Population Of the Process Evaluationmentioning
confidence: 99%